Internet Addiction Research in The School of Vocational Studies: Evidence from Turkey - Kurt, Doğuş; Tekin, Abdulkadir (Int Scientific Conference SGEM, 14, Kilment Ohridsky BLVD, Sofia, 1797, Bulgaria, 2008)
As a growing trend in the world, internet-based remote education both in governmental and private education institutes is getting popular in Turkey as it is to be all over the world. Internet-based education models give learners the chance to interact with the system. The aim of this research is to examine the relationship between personality and internet addiction of the students of Vocational school in a few of private University in Istanbul, Turkey. There is a significant correlation between the student personality which are depicted via adjective checklist and the student' internet addiction. Adjective Check List (ACL) items consist of adjectives which are words and/or phrases used for daily descriptions in Turkish Language. The scale composed of 25 items is examined for psychometric properties and internal consistency. In this research, Internet Addiction Inventory and ACL were conducted at the same time to a sample of 254 students of School of Vocational Studies. Internet addiction and personality correlates of ACL are of interest oil two counts. It is important to know what variables may be confounded with tendency of internet, usage.
Keywords: internet addiction; adjective checklist; vocational studies